Electromagnetic waves in layered conductors and superlattices in a magnetic field - Gvozdikov, V. M.; Vega-Monroy, R. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
The collective electromagnetic wave excitations in layered conductors in an external quantizing magnetic field are studied theoretically. A set of coupled equations for the electric field components and the Greens functions describing collective electromagnetic modes in such a system within the linear-response approach are obtained on the basis of a model of conducting planes embedded into a dielectric matrix. These equations, written in the layer-site representation, provide a basis for studies of the electromagnetic waves in the general case which does not imply either the spatial uniformity across the layers or the homogenity within the conducting planes. The dispersion equations are obtained for the uniform and homogeneous layered conductors, which give a rich structure of collective electromagnetic modes in layered conductors in an external magnetic field. The dispersion and damping of helicons in layered conductors in the regimes of conventional and quantum Hall effects have been studied, both analytically and numerically. Two new modes propagating perpendicular to the magnetic field with frequencies of the order of the plasma frequency have been found